The Short Lipopeptides (C10)2-KKKK-NH2 and (C12)2-KKKK-NH2 Protect HaCaT Keratinocytes from Bacterial Damage Caused by Staphylococcus aureus Infection in a Co-Culture Model - Kirsten Reddersen; Katarzyna E. Greber; Izabela Korona-Glowniak; Cornelia Wiegand (MDPI AG, 2020)
The search for new antimicrobial strategies is of major importance since there is a growing resistance of both bacteria and fungi to existing antimicrobials. Lipopeptides are promising and potent antimicrobial compounds. For translation into clinically useful molecules, effectiveness of peptide treatment against human infections must be proved in complex in vitro wound models. The aim of this study was to examine if the synthesized short lipopeptides (C10)2-KKKK-NH2 and (C12)2-KKKK-NH2 can protect HaCaT keratinocytes from bacterial damage caused by Staphylococcus aureus infection in a coculture model. After 1 h, 24 h, and 48 h incubation, cellular ATP level and release of the cytotoxicity marker LDH as well as the proinflammatory cytokines interleukin-6 and interleukin-1α were measured. Infection of the keratinocytes resulted in strong bacterial damage of HaCaT cells along with low cellular ATP levels and high release of LDH, IL-6, and IL-1α after 24 h and 48 h. Incubation of the infected human keratinocytes with (C10)2-KKKK-NH2 and (C12)2-KKKK-NH2 resulted in protection of the keratinocytes from bacterial damage caused by Staphylococcus aureus infection with ATP, LDH, IL-6, and IL-1α levels comparable to the untreated control. Hence, both synthesized lipopeptides are promising candidates with high therapeutic potential in dermatology for the treatment of topical infections.